2021
DOI: 10.1111/mec.16125
|View full text |Cite
|
Sign up to set email alerts
|

Peatland microbial community responses to plant functional group and drought are depth‐dependent

Abstract: Peatlands store one‐third of Earth's soil carbon, the stability of which is uncertain due to climate change‐driven shifts in hydrology and vegetation, and consequent impacts on microbial communities that mediate decomposition. Peatland carbon cycling varies over steep physicochemical gradients characterizing vertical peat profiles. However, it is unclear how drought‐mediated changes in plant functional groups (PFGs) and water table (WT) levels affect microbial communities at different depths. We combined a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 91 publications
4
25
0
Order By: Relevance
“…In contrast to prokaryotes, soil fungal community structure was not affected by soil depth in the intact bog, consistent with Wang et al (2019) who studied minerotrophic fens in China using a similar sampling design to ours, but in contrast with Lamit et al (2017Lamit et al ( , 2021 who found dramatic shifts in fungal community structure with depth. Furthermore, it is important to note that marginal sampling effort in our study may have affected the detectability of an effect of soil depth on fungal communities, similarly to Wang et al (2019) and in contrast to Lamit et al (2017Lamit et al ( , 2021 where sampling effort was greater. This is farther re ected in the lack of overall compositional shifts in soil fungi in our study, although phyla and functional guilds changed with soil depth.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast to prokaryotes, soil fungal community structure was not affected by soil depth in the intact bog, consistent with Wang et al (2019) who studied minerotrophic fens in China using a similar sampling design to ours, but in contrast with Lamit et al (2017Lamit et al ( , 2021 who found dramatic shifts in fungal community structure with depth. Furthermore, it is important to note that marginal sampling effort in our study may have affected the detectability of an effect of soil depth on fungal communities, similarly to Wang et al (2019) and in contrast to Lamit et al (2017Lamit et al ( , 2021 where sampling effort was greater. This is farther re ected in the lack of overall compositional shifts in soil fungi in our study, although phyla and functional guilds changed with soil depth.…”
Section: Discussionsupporting
confidence: 89%
“…Whilst microbial biomass has been shown to be typically high across all peat depths, microbial composition varies with peat depth as it is shaped by many factors, including moisture and oxygen availability [23,69], changes in substrate and redox potential [11,70], and carbon and soil nutrient dynamics [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a loss of living Sphagnum will lead to the subsidence of bare peat and the subsequent saturated conditions are not favorable for the growth of ericaceous shrubs. The significant correlation between the abundance of ericaceous shrubs and the relative abundance of ErMF is in line with the finding that the removal of Ericaceae can cause a remarkable decrease in ErMF abundance ( Lamit et al, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…Although PFT abundance changed substantially after N and/or P additions, the anticipated cascading effect on the fungal community was weak, which is inconsistent with our second hypothesis. This may be because our surface peat cannot capture the complex vertical stratification of the fungal community associated with vascular plants with different rooting depths in peatlands (e.g., Lin et al, 2014 ; Lamit et al, 2021 ). Unexpectedly, even 2 years of N and/or P additions also significantly changed PFT abundance, but the effects were complex.…”
Section: Discussionmentioning
confidence: 99%